Leading local government during COVID-19: An empirical finding from Ghana - Godson Kwame Amegayibor (Annals of Human Resource Management Research, 2022)
Purpose: This is to look into the impact of leadership on employee output in the local governance sector during the COVID – 19 Era. Research Methodology: A quantitative and descriptive approach, as well as a census method, were used to sample 220 employees. A structured questionnaire was used to gather data, multiple linear regression was used to test hypotheses, and SPSS version 20 was used to input, process, and analyze data. Result: The findings demonstrate that visionary, laissez-faire, and servant leadership styles have a considerable impact on staff output. Furthermore, employees' output is unaffected by autocratic and charismatic leadership styles. Limitation: The research only investigated five different types of leadership styles. Within the central region, it was similarly limited to only one metropolitan assembly. Contribution: It was demonstrated by the theory that under the local government, some various forces and situations drive the organization's activities; thus, leadership should be ready to change and dynamically position themselves to handle issues that arise.